Adaptation of Information Systems Strategic Planning of Universities Using COBIT 2019 in Post Covid-19 - Harits, Abdurrahman; Rahmat Gernowo; Djatmiko Endro Suseno (Universitas Pendidikan Ganesha, 2022)
COVID-19 has changed universities in managing processes and services with more relevant systems. This is a challenge for universities to design strategies both during and after this pandemic ends. This study aims to apply the methodology and design principles of COBIT 2019 to adapt the operational model and strategic planning of higher education institutions in the post-pandemic period. The COVID-19 challenge has shown that digital information systems are a critical factor in ensuring robust business processes. This study uses Syarif Hidayatullah State Islamic University Jakarta as a case study, the results of calculation of institutional capability level are currently in the range of level 3 with desired capability level target being level 4, this means that governance in the agency has been carried out according to plan but is not ready to implement fully used after the pandemic. This research produces several that are useful as the best adaptation in the New Normal era.